2015
DOI: 10.15252/embj.201490252
|View full text |Cite
|
Sign up to set email alerts
|

Single cell tuning of Myc expression by antigen receptor signal strength and interleukin‐2 in T lymphocytes

Abstract: Myc controls the metabolic reprogramming that supports effector T cell differentiation. The expression of Myc is regulated by the T cell antigen receptor (TCR) and pro-inflammatory cytokines such as interleukin-2 (IL-2). We now show that the TCR is a digital switch for Myc mRNA and protein expression that allows the strength of the antigen stimulus to determine the frequency of T cells that express Myc. IL-2 signalling strength also directs Myc expression but in an analogue process that fine-tunes Myc quantity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
168
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 143 publications
(185 citation statements)
references
References 59 publications
5
168
0
1
Order By: Relevance
“…The results are in agreement with our prior understanding of Myc regulation in T cells, which is driven by TCR signals upon antigen encounter and maintained by IL-2 signaling at later stages (30). It is likely that weakly stimulated T cells are unable to produce sufficient IL-2 to sustain expression of Myc and, consequently, its target genes involved in ribosome biogenesis.…”
Section: Inefficient Ribosome Biogenesis In Lck −/− Cells Causes Loss Ofsupporting
confidence: 90%
See 4 more Smart Citations
“…The results are in agreement with our prior understanding of Myc regulation in T cells, which is driven by TCR signals upon antigen encounter and maintained by IL-2 signaling at later stages (30). It is likely that weakly stimulated T cells are unable to produce sufficient IL-2 to sustain expression of Myc and, consequently, its target genes involved in ribosome biogenesis.…”
Section: Inefficient Ribosome Biogenesis In Lck −/− Cells Causes Loss Ofsupporting
confidence: 90%
“…STAT5 is activated by IL-2 and has been shown to regulate the expression of various cyclins and CDKs required for cell cycle progression through the G1 and S phases (52). IL-2 signaling is also very important for maintaining Myc translation because Myc protein, but not mRNA, is lost when cytotoxic T cells (CTLs) are incubated with the JAK inhibitor tofacitinib (30,53). Preston et al showed that proinflammatory cytokines are required to maintain Myc protein abundance because, in T cells, these cytokines sustain expression of amino acid transporters, which in turn support the amino acid uptake required to replenish rapidly turning over Myc protein (30).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations